Impact of evaporative pads and cross ventilation on core body temperature and resting time of lactating cows - Smith, John F., 1962-; Bradford, Barry J.; Harner, Joseph P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A trial was conducted to determine the impact of evaporative cooling pads on core body temperature (CBT), time spent lying, and number of lying bouts of Holstein cows housed in cross-ventilated freestall facilities. Despite cool ambient conditions during the trial, cows without evaporative pads tended to have elevated CBT above 102°F for 2.3 more hours per day and elevated CBT above 102.5°F for 0.95 more hours per day than cows with evaporative pads. These trends were evident even though the stocking density of the freestalls was greater in the facility with evaporative pads than in the facility without pads (123 vs. 113%). Lying times and lying bouts did not differ between treatments. Results of this study indicate that CBT tended to be reduced when evaporative pads were used, even under relatively mild ambient conditions.
Dairy Research, 2009 is known as Dairy Day, 2009
Keywords: Dariy; Evaporative cooling; Heat stress; Body temperature; Water use